2011
DOI: 10.1186/1471-2458-11-231
|View full text |Cite
|
Sign up to set email alerts
|

Targeting young drinkers online: the effectiveness of a web-based brief alcohol intervention in reducing heavy drinking among college students: study protocol of a two-arm parallel group randomized controlled trial

Abstract: BackgroundThe prevalence of heavy drinking among college students and its associated health related consequences highlights an urgent need for alcohol prevention programs targeting 18 to 24 year olds. Nevertheless, current alcohol prevention programs in the Netherlands pay surprisingly little attention to the drinking patterns of this specific age group. The study described in this protocol will test the effectiveness of a web-based brief alcohol intervention that is aimed at reducing alcohol use among heavy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 42 publications
(56 reference statements)
0
32
0
2
Order By: Relevance
“…The remaining interventions were carried out in Europe (n = 18, 18%) [52, 53, 55, 56, 60, 61, 70, 81, 95, 98, 102, 104, 110, 116, 119, 127, 128, 148], Australasia (n = 8, 8%) [54, 65, 66, 105, 108, 120, 124, 149], Asia (n = 6, 6%) [64, 67, 71, 72, 107, 114], South America (n = 3, 3%) [69, 79, 83], Africa (n = 1, 1%) [76] and one intervention (1%) was implemented in multiple countries across two continents (USA, Ecuador, Peru and Brazil) [84]. The risk behaviours that were targeted in various intervention countries, separated by studies with young adult male participants only and studies with outcomes stratified by age/sex to include young adult males are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining interventions were carried out in Europe (n = 18, 18%) [52, 53, 55, 56, 60, 61, 70, 81, 95, 98, 102, 104, 110, 116, 119, 127, 128, 148], Australasia (n = 8, 8%) [54, 65, 66, 105, 108, 120, 124, 149], Asia (n = 6, 6%) [64, 67, 71, 72, 107, 114], South America (n = 3, 3%) [69, 79, 83], Africa (n = 1, 1%) [76] and one intervention (1%) was implemented in multiple countries across two continents (USA, Ecuador, Peru and Brazil) [84]. The risk behaviours that were targeted in various intervention countries, separated by studies with young adult male participants only and studies with outcomes stratified by age/sex to include young adult males are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Other prevalent settings included military/army (n = 11, 11%) [52, 60, 61, 69, 71, 72, 104, 110, 119, 127, 128] and internet (n = 8, 8%) [45, 85, 92, 113, 132, 139, 148, 149]. Five studies (5%) were delivered in multiple settings [83, 111, 120, 122, 145].…”
Section: Resultsmentioning
confidence: 99%
“…El consumo excesivo de alcohol en la población universitaria ha generado gran preocupación (3,20), lo que ha llevado al desarrollo de programas de intervención (15,18,19). Se observó que el nivel medio de la TAS se situaba por encima de los límites legales en Portugal (0,5g/l) (23), situación que demuestra la necesidad de analizar cuidadosamente la problemática en estudio, no solo por los efectos directos, sino también por sus consecuencias, especialmente su asociación con los accidentes de tráfico (3,19,26).…”
Section: Discusionunclassified
“…Los estudiantes universitarios también han sido objeto de este tipo de intervenciones, especialmente en relación al consumo de alcohol, dado que diversos autores afirman que la situación de los jóvenes respecto al consumo de alcohol es preocupante, particularmente por sus consecuencias, sobre todo en forma de accidentes de tráfico (14,15). Por esta razón, también se han desarrollado programas para abordar esta problemática concreta (16)(17)(18)(19)(20).…”
Section: Introductionunclassified
“…One week after the intervention, participants will receive weekly EMA measurements for 6 months and a final EMA measurement 9 months after the intervention. Both in the pre-tests and post-tests, EMA will be used to assess participants' alcohol use and alcohol-related cognitions (Voogt et al, 2011).…”
Section: Intervention Mappingmentioning
confidence: 99%